A high optical transparency coating and its preparation method and application
Through the thiol-olefin click reaction caused by ultraviolet light and the formation of a silicon-oxysilicon network, the use of natural extract monoterpene alcohol as the anti-fouling active ingredient solves the problem of difficulty in developing a high optical transparency anti-fouling coating in the prior art, and achieves efficient stain protection and environmentally friendly coating preparation.
Patent Information
- Application Number
- CN202311173399.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-09-12
AI Technical Summary
It is difficult to develop a high optical transparency antifouling coating that can effectively prevent pollution from adhesion in marine environments and freshwater aquariums, and does not use highly toxic antifouling agents to avoid environmental pollution.
The thiol-olefin click reaction triggered by ultraviolet light is used as the antifouling active ingredient, and combined with tetramethyl silicate or tetraethyl silicate and R-trimethoxysilane or R-triethoxysilane under acidic conditions to form a silicon-based composite antifouling coating with side chains or backbone monoterpenols.
The prepared coating has high optical transparency, light transmittance exceeds 95%, and has high antibacterial activity and high inhibitory properties of diatom green algae, and has good stain desorption ability.
Smart Images

Figure CN117089283B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of marine antifouling coatings, and in particular to a high optical transparency coating and a preparation method and application thereof. Background Art
[0002] With the rapid development of today's society, the development and utilization of marine resources is more urgent. However, marine fouling is attached to the surface of ship hulls, underwater equipment and underwater sensors, causing increased ship navigation resistance, failure of underwater equipment, and inaccurate underwater sensor signals. It is urgent to develop a coating that is suitable for the protection of ship hulls, underwater equipment and underwater sensors. Due to the requirements of underwater equipment and underwater sensors for optical transparency, it is necessary to develop an antifouling coating preparation technology with high antifouling activity to resist the attachment of marine fouling and avoid the increase in navigation resistance, blurred visual images, and inaccurate sensor signals caused by fouling attachment. At the same time, the fish tanks and equipment in freshwater aquariums are affected by the problem of decreased transparency caused by the attachment of freshwater green algae. Therefore, what needs to be developed is a protective coating that can be applied to both marine equipment and freshwater equipment. However, the current antifouling coatings usually use highly toxic antifouling agents as the main antifouling active groups, which not only affect the transparency of the coating, but also cause pollution to the marine environment and cause certain harm to marine life.
[0003] Zhou Feng et al., in Chinese invention patent CN113004752A, a transparent marine antifouling coating and its preparation method and application, used sulfonylation reaction to prepare an antifouling agent structure, and mixed it with the prepared binding resin to prepare a transparent marine antifouling coating. The process of preparing the antifouling agent structure by this method is relatively complicated, requiring solid-liquid separation and drying processes, which is very inconvenient to operate, and uses organic solvents such as acetonitrile and ethylene glycol butyl ether, which causes certain pollution.
[0004] Shan Jianwen, in his Chinese invention patent CN105152546A, a transparent antifouling coating material for glass, a transparent antifouling coating and a preparation method thereof, prepared an antifouling coating using a mixed dispersion of fumed silica nanoparticles, a low surface energy binder and a solvent. However, the process of preparing the coating requires wiping the glass surface with a cloth strip, which not only increases the difficulty of operation and makes it difficult to ensure the uniformity of the coating, but also limits the application field of the coating by only using glass as the substrate.
[0005] Chinese patent CN113754308A discloses a method for preparing a super-double-repellent antifouling transparent coating: first, quadrilateral hollow silica particles are prepared by a sol-gel method, and then mixed with fumed silica to construct a rough structure with concave micropores. Under the action of a silane coupling agent, 1H, 1H, 2H, 2H, perfluorodecyl triethoxysilane is used to modify it to obtain a super-double-repellent antifouling transparent coating. The coating prepared by the invention shows good light transmittance, and at the same time has excellent properties such as super-double-repellent, self-cleaning, and antifouling. However, the invention prepares quadrilateral hollow silica particles by a sol-gel method, and its preparation process is relatively complicated. Summary of the invention
[0006] In view of this, in order to solve the above technical problems, the purpose of the present invention is to provide a high optical transparency coating and a preparation method and application thereof. The high optical transparency coating prepared by the present invention has high antibacterial activity and high inhibition of diatom and green algae attachment properties.
[0007] The technical solutions adopted are:
[0008] A method for preparing a high optical transparency coating of the present invention comprises the following steps:
[0009] S1. The monoterpene alcohol and the thiol monomer are stirred and mixed, and then a photoinitiator is added, and then reacted under ultraviolet light to generate a solution A;
[0010] S2. Select tetramethyl silicate or tetraethyl silicate, select R1 trimethoxysilane or R2 triethoxysilane, and then select alcohols for mixing and stirring to obtain solution B; wherein R1 or R2 is methyl, ethyl, propyl, butyl, hexyl, pentyl, octyl, decyl, anthracenyl, vinyl, chloromethyl, allyl, cycloalkyl, aminopropyl, mercaptopropyl;
[0011] S3. gradually adding solution A dropwise to solution B, stirring, and reacting to obtain solution C;
[0012] S4. The acid solution was added dropwise to solution C and reacted at room temperature to obtain a uniform, transparent solution D;
[0013] S5. The solution D is allowed to stand, and then applied to the surface of the substrate by spin coating, dip coating, brush coating or spray coating;
[0014] S6. The substrate coated with solution D is placed in a dark place at room temperature to form a stable coating.
[0015] Further, in S1, the monoterpene alcohol includes one or more of geraniol, nerol, citronellol, menthol, borneol, linalool, and terpinene tetraol; the thiol monomer includes one or more of mercaptopropyltrimethoxysilane, mercaptopropyltriethoxysilane, 2-mercaptoethanol, thioglycerol, and dimercaptopropanol; the photoinitiator includes one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, benzoin dimethyl ether, and methyl benzoylformate.
[0016] Furthermore, in S1, the molar ratio of monoterpene alcohol to thiol monomer is 1:0.5-3; and the amount of photoinitiator added is 1%-10% of the total mass of monoterpene alcohol and thiol monomer.
[0017] Furthermore, in S2, the alcohol is one or more of methanol, ethanol, and isopropanol.
[0018] Furthermore, in S2, the mass ratio of the selected tetramethyl silicate or tetraethyl silicate, the selected alkyltrimethoxysilane or alkyltriethoxysilane, and the selected alcohol is 1:0.5-3:0.75-3.
[0019] Furthermore, in S3, the mass ratio of solution A to solution B is 0.01-1:1, and the rate of adding solution A to solution B is 0.2-10 drops per second.
[0020] Furthermore, in S4, the acid solution is hydrochloric acid or citric acid, and the concentration is 0.01-1 mol / L.
[0021] Furthermore, the reaction time in S1 is 0.5-24 hours; the reaction time in S3 is 5-120 minutes; the reaction time in S4 is 12-72 hours; the static time in S5 is 0.5-144 hours; and the dark placement time in S6 is 48-240 hours.
[0022] The high optical transparency coating of the present invention is prepared by the preparation method described in any of the above schemes.
[0023] The above-mentioned high optical transparency coating of the present invention is used on the surface of underwater equipment and sensors in the marine environment, or on the surface of fish tanks or culture equipment in freshwater aquariums, or on the surface of equipment including visual windows, detection windows, and underwater cameras of underwater vehicles.
[0024] In the above technical solution,
[0025] Technical description of step S1: This preparation method is to generate free radicals by decomposing the photoinitiator under ultraviolet light, and then initiate the thiol monomer to form the corresponding free radical structure, and synthesize the corresponding antifouling functional monomer through the click reaction between the thiol and the carbon-carbon double bond in the monoterpene alcohol.
[0026] Technical description of step S3: In order to prepare a uniform antifouling material, the prepared antifouling functional monomer is evenly dispersed in other raw materials to avoid problems such as gelation caused by local agglomeration.
[0027] Technical description of step S4: Under acidic conditions, tetramethyl silicate or tetraethyl silicate and the methoxy group or ethoxy group of R-trimethoxysilane or R-triethoxysilane are hydrolyzed to form silicate particles, and then the silicate ions are polycondensed to form a silicon-oxygen-silicon network, and the prepared antifouling active monomer is dispersed in the silicon-oxygen-silicon network in the form of a side chain or a main chain.
[0028] Technical description of step S5: The formed solution D is allowed to stand for a period of time to ensure that the added raw materials are fully reacted and mixed, so that the material has the characteristics of high uniformity. Due to the uniformity of the solution D, the solution can be coated on the surface of the substrate by spin coating, dip coating, brush coating or spray coating.
[0029] Technical description of step S6: By placing it in a dark place, the solvent in the original solution is ensured to evaporate gradually in a slow manner to avoid problems such as cracking of the coating due to excessive volatilization. During the solvent volatilization process, the raw materials that have not completely reacted are polycondensed again to form a stable coating.
[0030] The antifouling coating prepared by the above preparation process provided by the present invention can be applied to the protection of the surface of underwater visual equipment and the surface of freshwater aquarium maintenance equipment during seawater development.
[0031] The high optical transparency coating provided by the present invention first uses a thiol-olefin click reaction triggered by ultraviolet light, uses a natural extract monoterpene alcohol as an antifouling active ingredient, prepares an antifouling functional group, and then forms a siloxane network by hydrolyzing and polycondensing selected tetramethyl silicate or tetraethyl silicate and selected R1-based trimethoxysilane or R2-based triethoxysilane under acidic conditions, and the antifouling functional group is connected to the siloxane network through the hydroxyl group after hydrolysis, forming a side chain grafted monoterpene alcohol or a silicon-based composite antifouling coating containing monoterpene alcohol in the main chain. Due to the presence of the R1-based and R2-based structures, the coating of the siloxane network has certain hydrophobic properties, so the coating exhibits suitable low surface energy properties, and further, the monoterpene alcohol in the side chain or main chain structure of the coating gives the coating good antifouling ability.
[0032] According to the results of the examples, it can be proved that the antifouling coating prepared by the preparation method of the present invention has high optical transparency at a wavelength of 350-800nm, and the transmittance exceeds 95%, which can meet the antifouling requirements of underwater visual equipment and windows used in the marine field, and can also meet the antifouling requirements of fish tanks or culture equipment in the field of freshwater aquariums. The results of the anti-bacterial attachment experiment show that the coating can inhibit bacterial attachment; the results of the anti-diatom attachment test show that the coating has the performance of inhibiting diatom attachment; and the coating has good fouling desorption ability, and the diatom desorption rate exceeds 89%.
[0033] The high optical transparency coating of the present invention can be used for underwater equipment and sensor surface protection in marine environments, and can also be used for green algae attachment protection in fish tanks or culture equipment in freshwater aquariums. The present invention uses natural extract monoterpene alcohol as an antifouling active ingredient, which is environmentally friendly, and the monoterpene alcohol is introduced through a UV-induced thiol-olefin click reaction, which has the characteristics of high efficiency and high atomic economy. In the subsequent coating preparation process, the method is simple, no high temperature and high pressure equipment is used, and the solvents are all low-volatile solvents, and the preparation process and the use process still have good environmental friendliness.
[0034] The transparent marine antifouling coating of the present invention can be used for antifouling of underwater visual windows, visual equipment, and camera equipment. The preparation method of the antifouling coating is convenient, the operating conditions are mild, the solvent used is a low-volatile solvent, and it is environmentally friendly.
[0035] In summary, compared with the prior art, the present invention has the following advantages:
[0036] 1. The antifouling coating prepared by the present invention using natural extract monoterpene alcohol as the antifouling group is environmentally friendly.
[0037] 2. The method of introducing natural extract monoterpene alcohols in the present invention has the characteristics of high efficiency and high atom economy. At the same time, the synthesis process does not use high-volatile solvents, and the synthesis process is environmentally friendly.
[0038] 3. The process of preparing the coating of the present invention does not use heating equipment and has good economic efficiency.
[0039] 4. The present invention introduces natural extract monoterpene alcohol as an antifouling active group, so that the antifouling coating has good antifouling activity. At the same time, the prepared antifouling coating has suitable surface energy and good fouling desorption ability.
[0040] 5. The present invention aims to solve the problems of blurred and ineffective visual equipment surfaces caused by fouling and adhesion during the development of marine resources, and reduced ornamental value caused by green algae adhesion in freshwater aquariums. An anti-fouling coating with high optical transparency is invented using natural extract monoterpene alcohol as an anti-fouling active group. The coating has high antibacterial activity and high inhibition of diatom and green algae adhesion. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The optical photographs are of a glass sheet, a coating prepared in Example 1, and a coating prepared in Example 2.
[0042] Figure 2 The transparency test results of the glass sheet, the coating prepared in Example 1 and the coating prepared in Example 2 under the UV-visible light spectrum are shown in the figure. According to the results in the figure, it can be seen that in the wavelength range of 350 to 800 nm, the coatings have an optical transparency higher than 97%.
[0043] Figure 3 These are the experimental results of inhibiting bacterial adhesion on glass slides, the coating prepared in Example 1, and the coating prepared in Example 2.
[0044] Figure 4 The experimental results of inhibiting the attachment of Ampelopsis thaliana on glass sheets, the coating prepared in Example 1 and the coating prepared in Example 2 are shown.
[0045] Figure 5 The experimental results of the fouling desorption ability of the coating prepared in Example 1. DETAILED DESCRIPTION
[0046] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only partial embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] Example 1
[0048] A method for preparing a high optical transparency coating of this embodiment comprises the following steps:
[0049] Step 1: Preparation of key antifouling monomers: 1.54 g of linalool and 3.92 g of (3-mercaptopropyl)trimethoxysilane were stirred and mixed, and then a certain mass of 0.35 g of benzoin dimethyl ether was added, and then reacted under ultraviolet light for 2 hours to generate solution A;
[0050] Step 2: Preparation of a silicon-based resin matrix: 2.08 g of tetraethyl silicate, 2.76 g of n-octyltriethoxysilane and 4 g of isopropanol were mixed and stirred to obtain a solution B;
[0051] Step 3: Mixing of composite materials: Add 2.73 g of solution A to solution B at a rate of 1 drop per second and stir for a certain period of time to obtain solution C;
[0052] Step 4: Preparation of composite materials: 1.41 g of 0.1 mol / L hydrochloric acid solution was added dropwise to solution C, and reacted at room temperature for 24 h to obtain a uniform and transparent solution D;
[0053] Step 5: coating of the composite material: solution D was allowed to stand for 48 h and then coated on a glass sheet by spin coating;
[0054] Step 6: Place the substrate coated with solution D in a dark place at room temperature for 120 hours to form a stable coating.
[0055] The properties of the coatings examined according to the corresponding test methods are as follows:
[0056] Coating transmittance inspection: The coating transmittance was inspected by visual observation. A glass sheet coated with the anti-fouling material prepared in Example 1 was placed on a piece of white paper with a pattern printed on it. It can be clearly seen that the pattern on the paper can be clearly seen through the coating. The results are shown in FIG. Figure 1 At the same time, the transmittance of the coating in the 350-800nm band was investigated by UV-visible light spectroscopy. The transmittance of the coating exceeded 95%, proving the high optical transmittance of the coating. Figure 2 .
[0057] Investigation of anti-bacterial adhesion of coating: The uncoated glass sheet and the glass sheet coated with the anti-fouling material prepared in Example 1 were placed in a culture solution of bacteria (Escherichia coli, Staphylococcus aureus and Pseudomonas Xiamenensis) of the same concentration for 24 hours, after which the bacteria attached to the surface of the glass sheet and the coating prepared in Example 1 were washed off, and then coated on the surface of the solid culture medium and cultured for 24 hours. By comparing the number of colonies formed by the bacteria washed off the surface of the glass sheet and the coating prepared in Example 1, the corresponding pictures are shown in FIG. Figure 3 , based on the number of colonies on the glass sheet surface, the bacterial adhesion inhibition rate of the coating surface prepared in Example 1 was calculated, and the following data were obtained:
[0058] Xiamen Pseudoalteromonas antibacterial rate: 92.5%
[0059] Staphylococcus aureus: 89.2%
[0060] Antibacterial rate of Escherichia coli: 79.1%.
[0061] Investigation of coating resistance to diatom adhesion: A glass sheet without coating and a glass sheet coated with the antifouling material prepared in Example 1 were placed in the same concentration of culture solution of Ampelopsis fasciatus for 24 hours. The diatoms attached to the surface of the glass sheet and the coating prepared in Example 1 were observed by fluorescence microscopy. The corresponding pictures are shown in Figure 4 , based on the number of diatoms on the surface of the glass sheet, the diatom inhibition attachment rate on the surface of the coating prepared in Example 1 was calculated, and the following data were obtained:
[0062] The inhibition rate of attachment of double-browed algae is 92.8%.
[0063] Investigation of the fouling desorption ability of the coating: A glass sheet coated with the antifouling material prepared in Example 1 was placed in a culture solution of the same concentration of Diplococephala for 96 hours. The diatoms attached to the surface of the coating prepared in Example 1 were observed by fluorescence microscopy, and the coating was placed under a 30Pa water flow for flushing. The diatom attachment after flushing was observed by fluorescence microscopy. The corresponding pictures are shown in Figure 5 , taking the number of diatoms attached to the unwashed coating surface as a benchmark, the diatom desorption rate on the coating surface prepared in Example 1 was calculated.
[0064] The desorption rate of D. diffusa under 30Pa water flow is 91.8%.
[0065] The performance of the coating in inhibiting bacterial attachment and diatom attachment demonstrates the potential application of the coating prepared by the method in the field of marine antifouling, and the high optical transparency of the coating demonstrates the potential application of the coating in related fields.
[0066] Example 2
[0067] Referring to Example 1, the difference from Example 1 is that in the method for preparing a high optical transparency coating of this example, the mass of solution A added in step 3 is 3.28 g, and the other steps remain unchanged.
[0068] The relevant properties and shapes of the tested coatings are as follows, and the testing method is the same as in Example 1:
[0069] Xiamen Pseudoalteromonas antibacterial rate: 87.0%
[0070] Staphylococcus aureus: 91.7%
[0071] Antibacterial rate of Escherichia coli: 86.5%.
[0072] Double eyebrow algae inhibition attachment rate: 92.5%
[0073] The desorption rate of D. diffusa under 30Pa water flow is 89.3%.
[0074] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a high optical transparency coating, characterized in that: The following steps are involved: S1. The monoterpene alcohol and the thiol monomer are stirred and mixed, and then a photoinitiator is added, and then reacted under ultraviolet light to generate a solution A; S2. Select tetramethyl silicate or tetraethyl silicate, select R1 trimethoxysilane or R2 triethoxysilane, and then select alcohols for mixing and stirring to obtain solution B; wherein R1 or R2 is methyl, ethyl, propyl, butyl, hexyl, pentyl, octyl, decyl, anthracenyl, vinyl, chloromethyl, allyl, cycloalkyl, aminopropyl, mercaptopropyl; S3. gradually adding solution A dropwise to solution B, stirring, and reacting to obtain solution C; S4. The acid solution was added dropwise to solution C and reacted at room temperature to obtain a uniform, transparent solution D; S5. The solution D is allowed to stand, and then applied to the surface of the substrate by spin coating, dip coating, brush coating or spray coating; S6. The substrate coated with solution D is placed in a dark place at room temperature to form a stable coating.
2. The method for preparing a high optical transparency coating according to claim 1, characterized in that: In S1, the monoterpene alcohol includes one or more of geraniol, nerol, citronellol, menthol, borneol, linalool, and terpinene tetraol; the thiol monomer includes one or more of mercaptopropyltrimethoxysilane, mercaptopropyltriethoxysilane, 2-mercaptoethanol, thioglycerol, and dimercaptopropanol; the photoinitiator includes one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, benzoin dimethyl ether, and methyl benzoylformate.
3. The method for preparing a high optical transparency coating according to claim 1, characterized in that: In S1, the molar ratio of monoterpene alcohol to thiol monomer is 1:0.5-3; and the added amount of the photoinitiator is 1%-10% of the total mass of the monoterpene alcohol and thiol monomer.
4. The method for preparing a high optical transparency coating according to claim 1, characterized in that: In S2, the alcohol is one or more of methanol, ethanol, and isopropanol.
5. The method for preparing a high optical transparency coating according to claim 1, characterized in that: In S2, the mass ratio of the selected tetramethyl silicate or tetraethyl silicate, the selected alkyl trimethoxysilane or alkyl triethoxysilane, and the selected alcohol is 1:0.5-3:0.75-3.
6. The method for preparing a high optical transparency coating according to claim 1, characterized in that: In S3, the mass ratio of solution A to solution B is 0.01-1:1, and the rate of adding solution A to solution B is 0.2-10 drops per second.
7. The method for preparing a high optical transparency coating according to claim 1, characterized in that: In S4, the acid solution is hydrochloric acid or citric acid, and the concentration is 0.01-1 mol / L.
8. The method for preparing a high optical transparency coating according to claim 1, characterized in that: The reaction time in S1 is 0.5-24 h; the reaction time in S3 is 5-120 minutes; the reaction time in S4 is 12-72 h; the static time in S5 is 0.5-144 h; and the dark placement time in S6 is 48-240 h.
9. A high optical transparency coating, characterized in that: The invention is prepared by the preparation method described in any one of claims 1 to 8.
10. Application of the high optical transparency coating of claim 9 on the surface of underwater equipment and sensors in marine environments, or on the surface of fish tanks or culture equipment in freshwater aquariums, or on the surface of equipment including visual windows, detection windows, and underwater cameras of underwater vehicles.
Citation Information
Patent Citations
Transparent antifouling coating material used for glass, and transparent antifouling coating and preparation method thereof
CN105152546A
Transparent marine anti-fouling paint as well as preparation method and application thereof
CN113004752A
Preparation method of super-amphiphobic antifouling transparent coating
CN113754308A